COVID-19 self-medication practices among slum dwellers in Jinja City, Uganda - Prossy Nakito; Arnold Tigaiza; Emmanuel Obuya; Geofrey Musinguzi; Dathan Byonanebye (Journal of Interventional Epidemiology and Public Health)
Introduction: Self-medication is one of the elements of self-care, which the World Health Organization (WHO) defines as the selection and use of medicines to treat selfidentified symptoms or ailments without consulting a physician. Self-medication is a worldwide public health concern, and the COVID-19 pandemic exacerbated it. Uganda was hit by two waves from April to June 2021, the second of which was more severe, resulting in lockdowns and quarantine. Effective COVID-19 treatments were difficult to obtain in Africa, and government treatment guidelines focused on symptom management. This increased the likelihood of self-medication practices in communities battling COVID-19 symptoms, especially slums. We identified selfmedication practices for COVID-19 prevention, treatment, and management among Jinja City slum dwellers so that appropriate educational, regulatory, and administrative measures could be developed to address this public health challenge. Methods: A cross-sectional study was conducted among urban slum dwellers randomly selected from slums in Jinja city. Households were proportionately recruited from the slums and an adult who had self-medicated for COVID-19 during 2021 was enrolled from each household. An electronic semi-structured interviewer-administered questionnaire was used to collect quantitative data. The data were imported into STATA version 14.0 for analysis. Self-medication practices for COVID-19 were also reported as frequencies and proportions using univariate analysis. Results: More than half, 58.1% (262/451) of the respondents reported using concoctions, 52.6% (237/451) used conventional medicine, and 41.2% (186/451) reported using herbal medicine for self-medication of COVID-19. Among the respondents who used concoctions, 95.0% (249/262) drank boiled concoctions, 68.3% (179/262) steamed concoctions. Among the 237 respondents who used conventional medicine 69.6% (165/237) self-medicated with vitamin C, 57.8% (137/237) with azithromycin, 55.7% (132/237) with paracetamol, and 54.9% (130/237) with zinc tablets. Conclusion: Majority of the slum dwellers self-medicated with conventional medicines or with herbal concoctions for COVID-19 prevention or treatment. The agents used for self-medications included antibiotics and potentially toxic agents. Pharmaceutical regulatory agents and public health agencies should conduct routine public awareness campaigns about the dangers of irrational drug use.